Balancing Religious Identity and Globalization: Leadership Motivations for Internationalization in Indonesian Islamic Universities - Syahriani, Ririn (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
This study investigates the motivations of Islamic university leaders in Indonesia regarding the implementation of internationalization, focusing on religious identity, adherence to national policies, and enhancement of institutional reputation. A qualitative case study approach was employed to collect data via semi-structured interviews with seven leaders from two Islamic universities: one public (Rose University) and one private (Tulip University). The findings indicate that leaders of private universities explicitly perceive internationalization as both an Islamic mission and a strategy for enhancing academic reputation. In contrast, state universities prioritize internationalization primarily as a means of adhering to national policies and securing institutional accreditation to enhance global competitiveness. This study presents a novel perspective, indicating that the internationalization of Islamic higher education is influenced not only by academic and economic factors but also significantly by elements of religious ideology.